O conceito de stato de Maquiavel: elementos constitutivos da modernidade estatal - Benetti, Fabiana de Jesus (2010)
Machiavelli wrote his political works using the terms for which does not offer a conceptual systematization. Among them we highlight the word stato. The study about this word allows observing the conceptual diversity left by the author, a multiplicity of uses without a precise definition that allows completely understand the term. Given the research on the significance of stato and the number of times it appears in Prince, we can affirm that this work is the work of complex stato in Machiavelli. The word is found 116 times and the term is used in different meanings, in complex and polysemic meanings (this datum will not limit our search to the referred work, but it certainly will receive greater attention). The difficulty in finding a single and precise meaning of the word is understandable when it is considered that in the Renaissance the term was undergoing a transformation. The significance of stato, which previously corresponded to status and concerned a position or condition, transitioned to the Modern conception of the term, distinguished from all previously existing forms of elements, such as unity, the organization in accordance with a constitution and the sovereign power which gives it an own sphere of action, independent of any other power. It is because of this that we find in the writings of Machiavelli meanings may involve the notion of power, territory, government or even State in the modern sense. This thesis aims to demonstrate some evidence of this transition in the writings of the Florentine. From the confrontation of elements that characterize the term stato in Machiavelli and characteristic elements of the concept of the notion of the modern state, we will try to demonstrate that, although Machiavelli does not use the term in the full sense of the latter, in his political theory there are certain notions close to the Modern understanding of State.